CESifo World Economic Survey May 2007 - Gernot Nerb; Anna Stangl (CESifo World Economic Survey, 2007)
World Economic Climate: World Economic Climate remains stable - Economic Expectations: Favourable assessments of current economic situation and stable economic expectations - Inflation: Expectations for 2007 revised upwards - Interest Rates: Trend of rising interest rates - Currencies: Western European currencies – euro and UK pound – seen as overvalued - Special Topic: International investment protectionism in “strategic industry sectors”
Keywords: 330